1976
DOI: 10.1159/000231561
|View full text |Cite
|
Sign up to set email alerts
|

DNA Synthesis <i>in vitro</i> by Cells from Mice Immunized with Picryl Chloride: Effect of Injection of Immune Cells

Abstract: Mice were immunized with picryl chloride and the regional nodes taken at various times afterwards. These cells spontaneously synthesized DNA in vitro as measured by thymidine incorporation over an 18-hour period and the peak incorporation occurred when the cells were taken on day 3. When the mice were injected with cells taken 5 days after immunization with picryl chloride and then immunized, there was a depression of the spontaneous DNA synthesis in vitro. This was absent on day 2, most marked on day 3 and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…It has been previously reported that primary epicutaneous exposure to at least some sensitizing chemi cals (picryl chloride and oxazolone) induced a rapid induction of lymphocyte proliferation in draining lymph nodes which was maximal 3 days following ap plication and declined markedly thereafter [1,3,4], Similar results were obtained in the present study in which draining auricular LNC proliferation follow ing topical application of oxazolone to the ear was measured by 3H-TdR incorporation in vitro. Follow ing challenge with several concentrations (5, 1 and 0.5%) of oxazolone, proliferation was maximal in LNC populations isolated 72 h following exposure.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…It has been previously reported that primary epicutaneous exposure to at least some sensitizing chemi cals (picryl chloride and oxazolone) induced a rapid induction of lymphocyte proliferation in draining lymph nodes which was maximal 3 days following ap plication and declined markedly thereafter [1,3,4], Similar results were obtained in the present study in which draining auricular LNC proliferation follow ing topical application of oxazolone to the ear was measured by 3H-TdR incorporation in vitro. Follow ing challenge with several concentrations (5, 1 and 0.5%) of oxazolone, proliferation was maximal in LNC populations isolated 72 h following exposure.…”
Section: Resultssupporting
confidence: 88%
“…The proliferative activity of draining auricular lymph nodes was determined 3 days following challenge. A representative experi ment is illustrated in figure 5 and demonstrates that, although maximal contact sensitization required 72 h to develop following primary sensitization, systemic Although a number of previous reports have sug gested that the regulation of lymphocyte proliferative responses induced by topical exposure to chemicals is generally hapten-specific [6], there exist data which argue for at least limited antigenic cross-reactivity [2][3][4], To investigate further the specificity of the in duced depression of lymphocyte proliferation, experi ments were performed with oxazolone and the antigenically non-cross-reactive contact sensitizing chemi cal picryl chloride. Topical application of either chemical resulted in depression of auricular lymph node responses following ear challenge with oxazo lone or picryl chloride.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations